A study of efficacy of ormeloxifene in abnormal uterine bleeding of ovulatory disorders - G. M., Nandhini; P. B., Hiremath; Banu A., Shameera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abnormal uterine bleeding (AUB) of ovulatory disorders is defined as the state of abnormal bleeding from the genital tract without any clinically detectable organic, systemic and iatrogenic cause. AUB is one of the common gynaecological issues among the patients visiting the hospital as it could affect at least 1/3rd of women in the child bearing age. Ormeloxifene, a nonsteroidal, nonhormonal and selective estrogen receptor modulator is a highly safe drug in treating acute and abnormal menstrual bleeding. Methods: The 40 cases of heavy menstrual bleeding (HMB) with ovulatory disorder in the range of 40-52 years of age were treated with 60 mg ormeloxifene twice a week for first 12 weeks and once a week for next 12 weeks. The patients were evaluated for haemoglobin, pictorial blood loss assessment chart (PBAC) score and endometrial thickness before and after treatment. Results: A significant decrease in endometrial thickness and PBAC score was observed. Also, the level of haemoglobin is found to increase significantly from 8.4±0.8 to 9.9±0.7. In this study, following 6 months of treatment with ormeloxifene, 90% of cases had marked improvement in their symptoms, while 10% of the patients required surgical management i.e., hysterectomy. Amenorrhea was observed in 7.5% of total cases and hypomenorrhea in 5% cases. Conclusions: Based on these results we could conclude that ormeloxifene could be the drug of choice in patients with AUB as it is very safe with manageable side effects. This simple drug-based therapy has facilitated compliance, tolerability and noticeable reduction of symptoms resulting in satisfaction towards the treatment.